Legal Protection of Well-Known Marks Against Passing Off: A Comparative Perspective - Batubara, Dinda Aprilia; OK. Saidin; Edy Ikhsan (Jurist-Diction, 2025)
Passing off of well-known marks remains a persistent form of trademark infringement in many jurisdictions, including Indonesia and Singapore. This paper undertakes a comparative analysis of the two countries’ trademark regimes, intending to assess and improve Indonesia’s legal protection of well-known marks. The study employs normative legal research combined with comparative qualitative analysis of statutory provisions and judicial practice. The findings reveal that Singapore’s Trade Marks Act provides more comprehensive protection, with a detailed substantive framework addressing passing off, effective sanctions, and a legal culture that promotes compliance. By contrast, Indonesia’s legal framework is less developed, relying on limited statutory guidance and weaker enforcement. This disparity underscores the need for reform in Indonesia to ensure more effective protection of well-known marks. The paper concludes that Indonesia should adopt clearer substantive provisions and foster stronger compliance mechanisms to enhance legal certainty.